The Effectiveness of Basic Life Support (BLS) Counseling in Improving the Knowledge of SMAN 2 Cimalaka Students - Ayu Prameswari; Iis Aisyah; Ida Nurhidayah; Ria Inriyana; Heri Ridwan (Universitas Pahlawan Tuanku Tambusai, 2026)
Sudden out-of-hospital medical emergencies require a quick and appropriate response to minimize the risk of death and disability. Basic Life Assistance (BLS) is a series of first aid measures that maintain blood circulation and lung ventilation in victims of respiratory arrest or cardiac arrest. However, BLS knowledge and skills among the general public are still very limited, especially in Indonesia. This counseling aims to evaluate the effectiveness of BLS in increasing participants' knowledge. This study used a quasi-experimental design with a pretest-posttest approach of one group. The population of this study consisted of 30 BLS training participants in the school environment, dominated by 22 females (73.3%) and 8 males (26.7%), with an age range of 15–18 years.. The results showed a significant increase in average score from 24.6 in the pre-test to 31.6 in the post-test (p<0.001). It is interesting to note in this study that although males showed higher pretest scores (27.8 compared to 23.5), females experienced a greater increase in scores (7.5 compared to 5.5). These findings show the potential for BLS counseling to be effective in improving public knowledge, regardless of gender or previous training history.